2010
DOI: 10.1007/978-1-60761-895-9_15
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Nanoparticle Fabrication: Magnetic Nanoparticle Synthesis and Enzyme Immobilization

Abstract: Immobilized enzymes are drawing significant attention for potential commercial applications as biocatalysts by reducing operational expenses and by increasing process utilization of the enzymes. Typically, immobilized enzymes have greater thermal and operational stability at various pH values, ionic strengths and are more resistant to denaturation that the soluble native form of the enzyme. Also, immobilized enzymes can be recycled by utilizing the physical or chemical properties of the supporting material. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…48 In the current study, the stability of tPA in solution at 4°C was enhanced 9.5-fold as a result of binding to SiO 2 -MNP. Possible mechanisms leading to enhanced storage stability of tPA could be ascribed to the restriction of the conformation change of the drug after covalent binding with SiO 2 -MNP, thus preventing distortion and activity loss of the enzyme molecule.…”
Section: Activity Retention (%)mentioning
confidence: 46%
“…48 In the current study, the stability of tPA in solution at 4°C was enhanced 9.5-fold as a result of binding to SiO 2 -MNP. Possible mechanisms leading to enhanced storage stability of tPA could be ascribed to the restriction of the conformation change of the drug after covalent binding with SiO 2 -MNP, thus preventing distortion and activity loss of the enzyme molecule.…”
Section: Activity Retention (%)mentioning
confidence: 46%
“…Magnetic nanoparticles are most popular materials due to their high surface to volume ratio for loading a larger amount of lipase, lower mass transfer resistance for reacting with substrates and ease the way of separation from the reaction mixture by external magnetic field [7]. Naked-magnetic nanoparticles are not applicable directly for lipase immobilization and some suitable surface modification or functionalization on the nakedmagnetic nanoparticles are necessary before immobilizing lipase onto the nanoparticles [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Naked-magnetic nanoparticles are not applicable directly for lipase immobilization and some suitable surface modification or functionalization on the nakedmagnetic nanoparticles are necessary before immobilizing lipase onto the nanoparticles [7][8][9]. It has been found that some organosilane compounds like 3-aminopropyltriethyloxysilane (APTES), paminophenyltrimethoxysilane (APTS) and mercaptopropyltriethoxysilane (MPTES) can be used as the potential candidates for functionalizing or modifying the surface of the naked magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The use of magnetic nanoparticles as a support for immobilized enzymes has many advantages, for instance, higher specific surface area is obtained for binding a larger amount of enzymes, lower mass transfer resistance and less fouling are achieved, and immobilized enzymes can be selectively separated from a reaction mixture by magnetic field application [11]. Various surface modifications of magnetic nanoparticles, such as silanization, carbodiimide activation, and polyethylene glycol or polyvinyl alcohol spacing, aid binding of single or multienzyme systems to particles, whereas cross-linking using glutaraldehyde can also stabilize the attached enzymes [12]. To date, several attempts have been made to immobilize enzyme alcohol dehydrogenase (ADH) on superparamagnetic magnetite (Fe 3 O 4 ) nanoparticles using the glutaraldehyde covalent immobilization [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%